PERENCANAAN ARSITEKTUR SISTEM INFORMASI e-PROCUREMENT MENGGUNAKAN METODE VALUE MATRIX PADA PT CIPTA KARYA BERSATU - Sandy Kosasi (SISFOTENIKA, 2012)
Abstracts: The results of architectural planning of e-Procurement information system uses a  model approach to the concept of value chain with value matrix method. Analysis of the concept value matrix to describe a complete map of the business opportunities in order to frame the foundation for creating a competitive advantage in cyberspace. This includes an overview of the environment and the system used, such as source and purchase contracts, purchase methods, process guidelines and requirements, as well as the level of automationand technology purchases. Through the implementation of an integrated information system is expected to reach the stage of competence in business process synchronization, convergence, integrity and interoperability. The aim is to facilitate the flow of information in refining the management of electronic procurement in order to meet customer needs in atimely manner with predetermined specifications efficiently and effectively.Keywords : Architecture Planning, e-Procurement Information Systems, Value matrix concepts, Business process, Class Diagram